Genome wide landscaping of copy number variations for horse inter-breed variability - Nitesh Kumar Sharma; Prashant Singh; Bibek Saha; Anuradha Bhardwaj; Mir Asif Iquebal; Yash Pal; Varij Nayan; Sarika Jaiswal; Shiv Kumar Giri; Ram Avatar Legha; T. K. Bhattacharya; Dinesh Kumar; et al. (Animal Biotechnology)
Copy number variations (CNVs) have become widely acknowledged as a significant source of genomic variability and phenotypic variance. To understand the genetic variants in horses, CNVs from six Indian horse breeds, namely, Manipuri, Zanskari, Bhutia, Spiti, Kathiawari and Marwari were discovered using Axiom™ Equine Genotyping Array. These breeds differed in agro-climatic adaptation with distinct phenotypic characters. A total of 2668 autosomal CNVs and 381 CNV regions (CNVRs) were identified with PennCNV tool. DeepCNV was employed to re-validate to get 883 autosomal CNVs, of which 9.06% were singleton type. A total of 180 CNVRs were identified after DeepCNV filtering with the estimated length of 3.12 Kb–4.90 Mb. The functional analysis showed the majority of the CNVRs genes enriched for sensory perception and olfactory receptor activity. An Equine CNVs database, EqCNVdb (http://backlin.cabgrid.res.in/eqcnvdb/) was developed which catalogues detailed information on the horse CNVs, CNVRs and gene content within CNVRs. Also, three random CNVRs were validated with real-time polymerase chain reaction. These findings will aid in the understanding the horse genome and serve as a preliminary foundation for future CNV association research with commercially significant equine traits. The identification of CNVs and CNVRs would lead to better insights into genetic basis of important traits.